Efektivitas sempoa organisator hamil, anak dan ibu balita dalam perubahan perilaku pencegahan stunting - Lia Mulyanti; Indri Astuti Purwanti; Novita Nining Anggraini (Jurnal Kebidanan, 2020)
In Indonesia, approximately 37% (nearly 9 million) of toddlers are stunted. There are 11 regencies in Central Java, including 100 priority areas for stunting reduction by the government. The 3 districts that had the highest prevalence of stunting were Blora (55.06%), Grobogan (54.97%), and Demak (50.28%). This research uses quasy experiment with a sample of 16 pregnant women in the control group and the experimental group. The results of the study, 92,4% of most pregnant women have good stunting prevention behavior except the behavior of eating animal protein foods. Based on the results of a comparative test of stunting prevention behavior based on tool intervention that shows a significant difference in the behavior of respondents who intervened with an abacus tool (0.003). Conclusion there are differences in community behavior based on intervention with the SEMOHAI tool (p value = 0.003) but there is no significant difference in community behavior based on intervention with conventional tools (p value = 0.083), and there is a significant difference (p value = 0.025) change in behavior based on intervention tools with conventional tools.